Rinitis Alérgica y Factores Desencadenantes en personas atendidas en el Centro de Salud de la Parroquia Guadalupe, Provincia Zamora Chinchipe - Valverde Correa, Aldana Mickaela (2022)
Allergic rhinitis is the most frequent form of non-infectious rhinitis and is associated to an immune response mediated by IgE antibody in the presence of environmental or occupational allergens. The present research had the purpose of knowing the presence of allergic rhinitis, analyzing its triggering factors according to age and sex in patients of the health center of the Guadalupe Parish, Zamora Chinchipe Province, and describing the relationship between these variables. A quantitative, cross-sectional cohort approach was used, with a sample of 155 patients who met the inclusion criteria, to whom the diagnostic questionnaire of allergic rhinitis and the sociodemographic collection sheet were applied, obtaining 87 people with a diagnosis of allergic rhinitis, 61% (n=53) were women and 39% (n=34) men. In women the prevalent group was youth (19-26 years) and adulthood (27-59 years) representing 22% (n=19), in men the youth (19-26 years) group prevailed 23% (n=20). As for the triggering factors, exposure to dust predominated in 94% (n=82), followed by humid climate with 85% (n=72). The relationship between the variables, 44% (n=38) of the participants in the youth age group, showed a predominance of allergic rhinitis associated with dust. 38% (n=33) were related to exposure to epidermal derivatives and animal saliva, a value of p < 0.9993 was obtained. This shows that the variables are not significantly associated.